2021
DOI: 10.1088/2053-1583/ac1ea9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical bonding of termination species in 2D carbides investigated through valence band UPS/XPS of Ti3C2T x MXene

Abstract: Chemical bonding of termination species in 2D carbides investigated through valence band UPS/XPS of Ti 3 C 2 T x MXene To cite this article: Lars-Åke Näslund et al 2021 2D Mater. 8 045026 View the article online for updates and enhancements.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 46 publications
(93 reference statements)
4
24
1
Order By: Relevance
“…The XPS spectra presented in this work are obtained from two types of Ti 3 C 2 T x samples: freestanding Ti 3 C 2 T x film and thin film Ti 3 C 2 T x on sapphire substrate. The preparations of both the freestanding Ti 3 C 2 T x film and the thin film Ti 3 C 2 T x on sapphire substrate are presented in previous works [13,19,24,25]. The Ti 3 AlC 2 , and TiC samples were both thin films on sapphire substrates prepared through direct current magnetron sputtering of elemental Ti, Al, and C targets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XPS spectra presented in this work are obtained from two types of Ti 3 C 2 T x samples: freestanding Ti 3 C 2 T x film and thin film Ti 3 C 2 T x on sapphire substrate. The preparations of both the freestanding Ti 3 C 2 T x film and the thin film Ti 3 C 2 T x on sapphire substrate are presented in previous works [13,19,24,25]. The Ti 3 AlC 2 , and TiC samples were both thin films on sapphire substrates prepared through direct current magnetron sputtering of elemental Ti, Al, and C targets.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a freestanding Ti 3 C 2 T x film obtained from Ti 3 AlC 2 powders prepared in an alumina tube furnace is incorporated with small amounts of non-reacted TiC, oxidized components (TiO 2 and Al 2 O 3 ), and components from other side reactions. The fabrication of the freestanding Ti 3 C 2 T x film, which is a multi-step process that includes wet etching, cycles of washing, de-aerating, sonication, centrifugation, and filtering [24,25], might reduce the amount of impurities from the Ti 3 AlC 2 powders preparation but at the same time introduce new impurities in one or several of the Ti 3 C 2 T x processing steps, such as metal halides, alcohols, and graphite-like materials (Figs. 1 and 2).…”
Section: Freestanding Ti 3 C 2 T X Film Versus Thin Film Ti 3 C 2 T X...mentioning
confidence: 99%
“…A previous study has shown that the 0-4 eV region of the Ti 3 C 2 T x valence band comprises hybridized Ti-C orbitals. 54 Immediately after the MXene is exposed to oxygen plasma, the signal in this region weakens (inset of Fig. 5a), confirming the breaking of the Ti-C structures of the MXene.…”
Section: Work Functionmentioning
confidence: 65%
“…The feature near 7.2 eV in the VB‐XPS spectra originated from the interaction between Ti and O orbitals. [ 46 ] And its peak position shifts to higher binding energy for 2‐MX than p‐MX, implying a change in the O‐containing termination species, which is in line with the removal of ‐OH. Besides, the corresponding E VB , XPS of p‐MX and 2‐MX is measured to be 1.23 and 1.84 eV respectively.…”
Section: Resultsmentioning
confidence: 97%